Quality Control of Camille Beauty Face Mask Products Using Failure Mode and Effect Analysis Method : A Case Study - Fithri, Prima; Putra, Abim Dwi; Prabuwono, Anton Satria; Pawenary, Pawenary (LPPM Universitas Andalas, 2023)
Regarding criticism and suggestions from consumers, it shows that of the 881,140 products sold, there are 22,947 products that are considered manufacturing defects, with an average percentage of defective products per month of 2.71%, with several types of defects submitted by consumers through the survey. This is quite serious because it will provide a bad experience to consumers in using this product. Failure Mode and Effect Analysis (FMEA) is a method used to evaluate system design by considering existing failure modes in a machine or equipment component system and analyzing the consequences for the reliability of the system. Based on the method used, it was found that the highest RPN value was in a case of disability, namely causing itching, with an RPN value of 504, consisting of a severity value of 9, occurrence of 7 and detection of 8, with a percentage of RPN occurrences of 35%. Beased on this result, it proposes improvements to the priority types of product defects and other product defects.